Design and development of fully automated water sprinkler system for small agriculture field - Mohanasundram T.; Isa M.R.; Ismail I.N.; Zahari N.M.; Roslan M.E.; Mohamed H.; Vicki W.V. (American Institute of Physics Inc., 2023)
The automated sprinkler system is developed to reduce human effort to water their plant in their backyard. The objectives of the project is to design, develop and analyse the water sprinkler system. The water sprinkler head was designed in solid works. The created design is then optimised using ANSYS FLUENT which the outlet of the water sprinkler head varies. The velocity and pressure is observed from the simulation through ANSYS FLUENT. Based on the result found that 1mm diameter outlet has highest velocity 2.07 m/s and highest pressure 105.64 Pa. The fabricated prototype then tested with developed automated system in UNITEN. The result of the test shows that the sprinkler height of 0.6 m from the ground projects the water the furthest at 0.35 m. 2019 Author(s).